Ultraviolet-Sensor Based on Tin-Doped Zinc Oxide Thin Films Grown by Spray Pyrolysis - Valdes, Matias Hernan (2024)
The development of sensors that can monitor ultraviolet radiation has many implications for daily life, and even more so if the focus is on low-cost solution processes and the use of eco-friendly materials. In this study, we produced a UV-sensor based on Sn-doped ZnO thin films grown by spray pyrolysis, with a doping content ranging from 1 to 10 at.%. The study focuses on the characterization of the films and the device, and their potential for UV detection. Structural analysis via XRD, FESEM, and STEM confirms the polycrystalline nature of the films, with a hexagonal sin-gle-phase wurtzite structure of ZnO. Although the dopant content in the films was widely varied, optoelectronic properties such as transmittance, resistivity, energy gap, density, and carrier mobility are not significantly modified. Sprayed Sn-doped ZnO films demonstrated high sensitivity to ultraviolet light, whether monochromatic or that coming from solar radiation. Outdoor measurements showed promising performance of the UV-sensor, indicating its potential applicability for real-time UV monitoring and potential use. Overall, sprayed Sn-doped ZnO thin films offer a viable and low-cost solution for the fabrication of UV-sensors with desirable properties such as a wide and direct bandgap, high sensitivity, and ease of fabrication.